Using Flashcards and Story Chains to Support Deep Learning in Grammar Class - Yeni Ikawati (Universitas Muria Kudus, 2025)
Teaching grammar often becomes a challenge in the classroom, especially when students are not confident to use English actively. The purpose of this study was to examine how flashcards and story chain activities could support deep learning in grammar instruction. This classroom practice was carried out with Grade X students at MA NU Nurussalam Gebog Kudus using a qualitative descriptive design. The lesson focused on adverbs of time, past simple, and past progressive tenses. Flashcards were used to help students identify and use adverbs of time in context, while story chain activities encouraged collaboration, where each student continued the story using the target grammar. These activities supported stimulation, exploration, collaboration, and reflectionâ€”the four stages of deep learning. The results showed that students were more engaged, demonstrated better understanding of grammar patterns, and applied them in recounting past events. Despite challenges such as limited vocabulary and reliance on scaffolding in Bahasa Indonesia, the approach proved effective in creating meaningful grammar practice and empowering students to build confidence in using English.Â